Exploring the Relationship Between Translation Students’ Personality Characteristics and Their Preference for Using Translation Strategies - Navidinia, Hossein; Imani, Parisa; Mobaraki, Mohsen (Indonesian Journal of Applied Linguistics, 2021)
For years, research in translation studies has focused on examining linguistic and sociolinguistic features of the source and target texts, and the active role of a translator as an important agent in the process of producing a target text has been underestimated. However, recently the importance of the influential role of translators and their personal characteristics have been highlighted. Considering this important development, the aim of this study was to examine the possible relationship between translation students’ personality characteristics and their preference for using translation strategies based on two translation strategy models proposed by Vinay and Darblenet (1995) and Venuti (1995). For so doing, 100 translation students were asked to answer the NEO FFM Personality scale and choose one of the suggested translations for each of the 69 sentences designed based on the translation models. The data were analyzed using SPSS (version 22) and Smart PLS (3.0) software. The findings indicated that some of the participants’ personality traits like neuroticism and openness to experience had a significant relationship with the use of some translation strategies such as adaptation, modulation and borrowing. The findings were discussed and the implications were made.